Perspektif Al-Qur’an Tentang Posisi Manusia Dalam Memakmurkan Alam Raya - Abdullah, Dudung (Jurusan Hukum Tatanegara Fakultas Syariah dan Hukum Universitas Islam Negeri Alauddin, 2016)
God's authority and control the universe of natural riches to humans and all other creatures with affection. Man was created as a servant of God and inheritors of God. As inheritors of God, he has the authority, potency, and the freedom to prosper nature of the universe that have been subjugated Allah. With the ability of mind, intelligence and vision science, humans are able to organize and preserve lives peacefully with other creatures. Humans as bearers of the message of God to inhabit the universe must be within the law and the rule of God and never against sunatullah which he set forth.